Heterogeneous IgE reactivities to Staphylococcus pseudintermedius strains in dogs with atopic dermatitis, and the identification of DM13-domain-containing protein as a bacterial IgE-reactive molecule. Issue 1 (22nd February 2022) - Takemura-Uchiyama, Iyo; Tsurui, Hiroki; Shimakura, Hidekatsu; Nasukawa, Tadahiro; Imanishi, Ichiro; Uchiyama, Jumpei; Fukuyama, Tomoki; Sakamoto, Shuji; Morisawa, Keiko; Fujimura, Masato; Murakami, Hironobu; Kanamaru, Shuji; et al.
Abstract: Staphylococcus pseudintermedius is one of the major pathogens causing canine skin infection. In canine atopic dermatitis (AD), heterogeneous strains of S. pseudintermedius reside on the affected skin site. Because an increase in specific IgE to this bacterium has been reported, S. pseudintermedius is likely to exacerbate the severity of canine AD. In this study, the IgE reactivities to various S. pseudintermedius strains and the IgE-reactive molecules of S. pseudintermedius were investigated. First, examining the IgE reactivities to eight strains of S. pseudintermedius using 141 sera of AD dogs, strain variation of S. pseudintermedius showed 10–63% of the IgE reactivities. This is different from the expected result based on the concept of Staphylococcus aureus clonality in AD patients. Moreover, according to the western blot analysis, there were more than four proteins reactive to IgE. Subsequently, the analysis of the common IgE-reactive protein at ∼15 kDa confirmed that the DM13-domain-containing protein was reactive in AD dogs, which is not coincident with any S. aureus IgE-reactive molecules. Considering these, S. pseudintermedius is likely to exacerbate AD severity in dogs, slightly different from the case of S. aureus in human AD. Abstract : IgE reactivities to Staphylococcus pseudintermedius .